A rare finding of mites (Arachnida: Acari: Leeuwenhoekiidae) parasitising a whip spider (Arachnida: Amblypygi: Charinidae) - Goncalves-Souza, Thiago; Giupponi, Alessandro P. L.; Hernandes, Fablo A. [UNESP] (Folia Parasitologica, 2014)
Twelve larvae of unidentified species of Odontacarus Ewing, 1929 (Acari: Leeuwenhoekiidae) were found parasitising an adult male whip spider Charinus brasilianus Weygoldt (Charinidae) in Santa Teresa, mountainous region of Espirito Santo state, southeastern Brazil. These larvae occurred in the intersegmental membrane of prosoma and legs. This is the first report of ectoparasitic mites infecting a charinid whip spider and the first record of leeuwenhoekiid mites parasitising an invertebrate host. We suggest that future studies are essential to understand the reasons why these events of parasitism are so rare in the order Amblypygi.
Keywords: ectoparasitism; chigger mites